LncRNAs LY86-AS1 and VIM-AS1 Distinguish Plasma Cell Leukemia Patients from Multiple Myeloma Patients - Bútová, Romana; Vychytilová-Faltejsková, Petra; Gregorová, Jana; Radová, Lenka; Almáši, Martina; Bezděková, Renata; Brožová, Lucie; Jarkovský, Jiří; Knechtová, Zdeňka; Štork, Martin; Pour, Luděk; Ševčíková, Sabina (Biomedicines, 2021)
Long non-coding RNAs (lncRNAs) are functional RNAs longer than 200 nucleotides. Due to modern genomic techniques, the involvement of lncRNAs in tumorigenesis has been revealed; however, information concerning lncRNA interplay in multiple myeloma (MM) and plasma cell leukemia (PCL) is virtually absent. Herein, we aimed to identify the lncRNAs involved in MM to PCL progression. We investigated representative datasets of MM and PCL patients using next-generation sequencing. In total, 13 deregulated lncRNAs (p < 0.00025) were identified; four of them were chosen for further validation in an independent set of MM and PCL patients by RT-qPCR. The obtained results proved the significant downregulation of lymphocyte antigen antisense RNA 1 (LY86-AS1) and VIM antisense RNA 1 (VIM-AS1) in PCL compared to MM. Importantly, these two lncRNAs could be involved in the progression of MM into PCL; thus, they could serve as promising novel biomarkers of MM progression.
Keywords: multiple myeloma; biomarkers; next-generation sequencing; long non-coding RNA; disease progression; plasma cell leukemia